Risk factors for blood transfusion in patients undergoing high‐order Cesarean delivery. Issue 11 (7th August 2017) - Spiegelman, Jessica; Mourad, Mirella; Melka, Stephanie; Gupta, Simi; Lam‐Rachlin, Jennifer; Rebarber, Andrei; Saltzman, Daniel H.; Fox, Nathan S.
Abstract : BACKGROUND: The objective was to identify risk factors associated with blood transfusion in patients undergoing high‐order Cesarean delivery (CD). STUDY DESIGN AND METHODS: This was a retrospective cohort study of patients undergoing third or more CD by a single maternal‐fetal medicine practice between 2005 and 2016. We compared risk factors between women who did and did not receive a red blood cell transfusion during the operation or before discharge. Repeat analysis was performed after excluding women with placenta previa. RESULTS: A total of 514 patients were included, 18 of whom (3.5%; 95% confidence interval [CI], 2.2%‐5.5%) received a blood transfusion. Placenta previa was the most significant risk factor for transfusion (61.1% of patients who received a transfusion vs. 1% of patients who did not; p < 0.001). Patients with a placenta previa had a 68.8% likelihood of requiring a blood transfusion. After women who had placenta previa were excluded, the incidence of blood transfusion was seven of 498 (1.4%; 95% CI, 0.7%‐2.9%). Risk factors significantly associated with blood transfusion in the absence of previa were prophylactic anticoagulation during pregnancy and having labored. The incidence of transfusion in patients with no placenta previa, no anticoagulation, and no labor was 0.7% (95% CI, 0.3%‐2.1%). Placenta previa was the most predictive risk factor for transfusion with a positive predictive value of 68.8% and a negative predictive value of 98.4%. CONCLUSION: In patients undergoing a third or more CD, only placenta previa, prophylactic anticoagulation during pregnancy, and having labored are independently associated with requiring a blood transfusion. These data can be used to guide physician ordering of prepared blood products preoperatively.